Wnt-controlled sphingolipids modulate Anthrax Toxin Receptor palmitoylation to regulate oriented mitosis in zebrafish - I. Castanon (Nature Portfolio, 2020)
During development, oriented cell division is important to proper body axis extension. Here, the authors show that sphingolipids are required to direct spindle rotation and oriented mitosis via Anthrax receptor palmitoylation in zebrafish gastrulation.